(66+30)*x=360+30*x

Simple and best practice solution for (66+30)*x=360+30*x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (66+30)*x=360+30*x equation:


Simplifying
(66 + 30) * x = 360 + 30x

Combine like terms: 66 + 30 = 96
(96) * x = 360 + 30x

Solving
96x = 360 + 30x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-30x' to each side of the equation.
96x + -30x = 360 + 30x + -30x

Combine like terms: 96x + -30x = 66x
66x = 360 + 30x + -30x

Combine like terms: 30x + -30x = 0
66x = 360 + 0
66x = 360

Divide each side by '66'.
x = 5.454545455

Simplifying
x = 5.454545455

See similar equations:

| 6×1/4 | | 5/1=1/3 | | 27x=0 | | (66+30x)=360+30x | | 9/32/5 | | 3x+20+10x-21=90 | | -4x+9y=81 | | (-5-1)-2f=-2(3-5) | | (5x-7)(7x+9)=0 | | -100(x+4)+54=-13-13 | | 5(x-2)=-9(x+1)+17 | | 12/21=18/x | | 66+30x=360+30x | | (5x+5)(5x^2+3x+2)= | | 3(4z+3)= | | -3(7.5+-3y)-2y=5.5 | | 6/5 | | 23-13=2(x-8) | | 4d-5(d-1)=3-d+2 | | 3p+5=p+15 | | 6/7(-4/9-1/7x)=-62/147 | | X=3-12 | | -12y+10=46 | | 5+7x+16+x=11x-3-x | | 6k+5=20 | | 9y^2-12y-1=0 | | h(t)=20-16t*2+32t | | 12s=8+2x(5s+3) | | 5(x-4)=-7(x+3)+45 | | 11x^2(144)=0 | | 3j^2-20j=12 | | 2x-9+87-9x*9+1=100 |

Equations solver categories